2003
DOI: 10.1002/pc.10022
|View full text |Cite
|
Sign up to set email alerts
|

Using textile topography to analyze X‐ray CT data of composite microstructure

Abstract: The 3-dimensional yam architecture in a 2-dimensional woven fabric reinforced composite is nonuniform. Many structural features appear that are not obvious from consideration only of the yarn architecture in the single layer textile fabric. A compIete set of 3-dimensional image data was acquired for a representative volume of the composite using X-ray micro-computed tomography. Extensive image analysis was, however, necessary to reveal the yarn architecture due to relatively low signal-to-noise ratio and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This method is also routinely used to deliver detailed three-dimensional images of the objects of interest. Up to now, no studies of textiles in this manner have been reported, although Parnas et al [12] examined the yarn structure and architecture in fibre-reinforced composite materials using µCT. Here we apply µCT to the study of moisture transport in five multilayered textile combinations.…”
mentioning
confidence: 99%
“…This method is also routinely used to deliver detailed three-dimensional images of the objects of interest. Up to now, no studies of textiles in this manner have been reported, although Parnas et al [12] examined the yarn structure and architecture in fibre-reinforced composite materials using µCT. Here we apply µCT to the study of moisture transport in five multilayered textile combinations.…”
mentioning
confidence: 99%
“…It not only focuses on the direct relationship between process parameters and properties, but also provides insight into how these properties are realized through the variation of microstructure. Specifically, it involves the integration of automated protocols for multimodal data, such as microstructural data obtained by electron microscopy 74 or micro‐CT scanning, 75 material property data obtained by experiments and simulations, as well as machine learning datasets. The intrinsic factors affecting the performance of AM‐CFRPCs from process will be further explored in the future.…”
Section: Resultsmentioning
confidence: 99%
“…'X-Ray CT has of course been used for many years to image biological features for medical research' (Parnas et al 2005(Parnas et al : 1920. X-ray imaging fragile textiles requires much experimentation to achieve the desired settings, prior and post scanning process.…”
Section: Ct Scanmentioning
confidence: 99%